Calculating the Number of Bacterial Colonies of Escherichia Coli in the Hands of Food Vendors Around Basic Schools, Sukagumiwang District - Fitriani, Hikmah; Sriwiyati, Kati; Fajar Islamy, Ilham (Riviera Publishing, 2025)
Diarrhea is still a public health problem in the Sukagumiwang sub-district area. Data of diarrhea sufferers in 2018 at the Sukagumiwang Community Health Center showed 331 patients of all ages, and there were 162 toddlers affected by diarrhea. The main factor for diarrhea is cleanliness in the processing of food consumed daily. The aim of this study is to find out the calculation of Escherichia Coli bacterial colonies in food vendors’ hands around the Elementary School Sukagumiwang sub-district area before and after using a hand sanitizer. This study is an experimental pretest-posttest group design study on the object of research by sampling using simple random sampling. The median number of Escherichia coli bacteria present in the hands of food vendors before washing their hands in elementary school Sukagumiwang sub-district was 62 CFU / cm2. The median number of Escherichia coli bacteria in the hands of food vendors after washing their hands in SD Sukagumiwang sub-district is 8 CFU / cm2. The Wilcoxon Signed Rank Test results show significant results with a value of p <0.001. There is a difference in the number of Escherichia coli bacteria before and after using a hand sanitizer on food vendors’ hands around the elementary schools in the Sukagumiwang sub-district area.